What's the Best Factor to Determining Firm Value? - Neneng Susanti; Nanda Gyska Restiana (University of Merdeka Malang, 2018)
This study aims to determine the factors that affect the firm value in the LQ-45 Index companies in Indonesia. Independent variables in this study are company size, company age, capital structure, financial performance, and company profit. This research uses purposive sampling method and multiple regression analysis with total sample 108 from 2013-2016. The result of the research shows that company size will negatively affect firm value will have an adverse effect on the company's growth so that investor interest will tend to decrease. Company age influences firm value so that it can increase trust for an investor to invest. Capital structure influences firm value so it can reduce the impact on company expense and the level of debt. The financial performance affects the firm value will have an impact on the increase of investors in the company, corporate profits negatively affect the firm value so it should be able to increase further the company sales in generating profits to be distributed to shareholders.JEL Classification: G32DOI: https://doi.org/10.26905/jkdp.v22i2.1529